2017
DOI: 10.1111/his.13322
|View full text |Cite
|
Sign up to set email alerts
|

Digital image analysis of HER2 immunohistochemistry in gastric‐ and oesophageal adenocarcinoma: a validation study on biopsies and surgical specimens

Abstract: Aims: To test the validity of diagnostics incorporating digital image analysis (DIA) for human epidermal growth factor 2 (HER2) immunohistochemistry (IHC) in gastro-oesophageal adenocarcinomas, as an alternative to current standard diagnostics using manual scoring. Methods and results: We included 319 consecutive gastro-oesophageal adenocarcinomas (232 biopsies and 87 surgical specimens). DIA was applied to determine HER2 IHC classification, using both standard breast cancer (BC) and modified gastro-oesophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Eyeball-based analysis had high sensitivity but low specificity (Figure 4); DIA could be more sensitive and more specific, at least compared to the eyeball-based analysis (Figure 4). Potential application of DIA to the evaluation of human epidermal growth factor receptor 2 (HER2) or programmed death ligand-1 (PDL-1) immunoreactivity was reported to provide a more objective and accurate prediction of therapeutic response than that of eyeball examinations [28,34], which was consistent with this study's results. In addition, evaluation of SSTR2 using DIA may also be useful in predicting the therapeutic efficacy of novel PRRT [21,22] and further studies are warranted to confirm this clinically important aspect.…”
Section: Discussionsupporting
confidence: 89%
“…Eyeball-based analysis had high sensitivity but low specificity (Figure 4); DIA could be more sensitive and more specific, at least compared to the eyeball-based analysis (Figure 4). Potential application of DIA to the evaluation of human epidermal growth factor receptor 2 (HER2) or programmed death ligand-1 (PDL-1) immunoreactivity was reported to provide a more objective and accurate prediction of therapeutic response than that of eyeball examinations [28,34], which was consistent with this study's results. In addition, evaluation of SSTR2 using DIA may also be useful in predicting the therapeutic efficacy of novel PRRT [21,22] and further studies are warranted to confirm this clinically important aspect.…”
Section: Discussionsupporting
confidence: 89%
“…DIA of Ki67 IHC in breast carcinoma offers a time‐saving and reproducible alternative to manual counting . Additionally, DIA of HER2 IHC in gastroesophageal adenocarcinomas proved to be a reliable alternative to manual scoring, reducing 2+ cases with high sensitivity (93.8–97.9%) and specificity (99.6%) . However, in comparison to breast carcinoma, HER2 scoring in gastroesophageal carcinoma is prone to more manual 2+ cases due to tumour heterogeneity and a low positivity threshold in biopsies (≥5 tumour cell clusters are sufficient).…”
Section: Discussionmentioning
confidence: 99%
“…DIA could reduce the number of 2+ cases requiring subsequent ISH testing, which may increase time‐ and cost‐efficiency in clinical practice . Our group previously found that DIA of HER2 IHC can reduce 2+ cases in gastroesophageal adenocarcinoma …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…1) have also received CE marking. Visiopharm’s QIA algorithm for HER2 IHC has demonstrated an accurate assessment of both breast carcinoma and gastric/esophageal adenocarcinoma 92,111,112. A recent study demonstrated that employing QIA to score HER2 IHC had excellent concordance with pathologists’ scores and accurately discriminated between HER2 FISH positive and negative cases 113…”
Section: Applications Of Biomarker Imaging Analysismentioning
confidence: 99%